2004
DOI: 10.1111/j.1399-3038.2004.00202.x
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and allergic diseases in schoolchildren: third cross‐sectional survey in the same primary school in Ankara, Turkey

Abstract: We investigated prevalence and determinants of asthma and allergic diseases in a cross-sectional survey of schoolchildren aged 6-14 in 2002. This was the third of a series of cross-sectional surveys, conducted in 1992 and 1997, in the same school in Ankara, Turkey. Questionnaire including information on house characteristics, dietary habits, past and current exposures and diseases were distributed to 1064 children (523 boys, 541 girls) and filled by the parents at home. Percentage of children having a pet was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 31 publications
3
33
1
4
Order By: Relevance
“…Although there is a trend towards increasing number of pet ownership in our country [29,30], it is still lower than European countries, where these sensitization rates change between 18.4% and 49.3% for cat and 16.1% and 56.0% for dog [6].…”
Section: Discussionmentioning
confidence: 83%
“…Although there is a trend towards increasing number of pet ownership in our country [29,30], it is still lower than European countries, where these sensitization rates change between 18.4% and 49.3% for cat and 16.1% and 56.0% for dog [6].…”
Section: Discussionmentioning
confidence: 83%
“…In a series of cross-sectional studies, in 5 years' intervals, since 1992 in the same school in Ankara, Turkey, we observed a negative trend for prevalence of asthma and allergic diseases in 2002 (8).…”
Section: Introductionmentioning
confidence: 82%
“…Children have been identified as a group sensitive to ETS because their respiratory and immune systems are not fully developed (2,3). The associations between ETS exposure and allergic diseases in children have been extensively investigated (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14); in most, but not all, studies, exposure to ETS is positively associated with wheeze, asthma, or eczema (4)(5)(6)(7)(8)(9)(10). On the other hand, epidemiological evidence of the effect of maternal smoking during pregnancy on allergic diseases is inconsistent (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26); studies have shown positive (15)(16)(17)(18)(19)(20)(21)(22)(23)(24), inverse (24), or no associations (21,(24)(25)(26) betwe...…”
Section: Introductionmentioning
confidence: 98%